African National Congress (ANC): Attainment of Power, Post Liberation Phases and Current Crisis (Historia, 2021)
EnglishFor much of 2005 and 2006 the ANC appeared to be tearing itself apart and was rocked by scandals and court cases affecting its Deputy President, Jacob Zuma, whose supporters rose in open defiance of the leadership of President Thabo Mbeki. This article traces the background to the current battle for succession to the presidency of the ANC and the country, and the consequent capacity to dispense patronage. It traces the process whereby the ANC transformed itself from an organisation engaged in insurrection to one where it is simultaneously mobilising and organising supporters and acting as the government of a conventional state. This dual status as organisation and government is seen as one of the key factors giving rise to centralisation in the presidency and conflict with the ANC mass membership and its allies, COSATU and SACP. There are nevertheless signs that what happens at the centre and the top may not be typical of the whole organisation. Unfortunately the range of experiences and understandings, in the various rural provinces have not yet been adequately recorded.   AfrikaansDie African National Congress (ANC): Magsverkryging, Na-Bevrydingsfases en Huidige Krisis Vir die grootste gedeelte van 2005 en 2006 het dit gelyk asof die ANC homself uitmekaarskeur en is dit geskud deur skandale en hofsake rakende die adjunk-president, Jacob Zuma, wie se ondersteuners openlik in opstand teen die leierskap van president Thabo Mbeki gekom het. Hierdie artikel ondersoek die agtergrond van die huidige opvolgingstryd betreffende die presidentskap van die ANC en die land, asook die gevolglike vermoë om begunstiging te verleen. Dit speur die proses waardeur die ANC homself van ŉ organisasie betrokke by oproer tot een wat tegelyk ondersteuners mobiliseer en organiseer, asook optree as die regering van ŉ konvensionele staat, omskep het. Hierdie tweevoudige status as beide organisasie en regering word beskou as een van die sleutelfaktore wat veroorsaak het dat sentralisering in die presidentskap plaasgevind het en vir konflik met die ANC se massa lidmaatskap en sy bondgenote, COSATU en die SAKP verantwoordelik was. Daar is nogtans tekens dat wat op die middel- en topvlak gebeur, nie noodwendig tipies van die hele organisasie is nie. Ongelukkig is die omvang van belewing en begrip in die onderskeie plattelandse provinsies nog nie na behore aangeteken nie.
Keywords: African National Congress (ANC); alliance; bureaucracy; centralization; Communists; corruption; crisis; democracy; government; leadership; battle; liberation; liberation movement; negotiations; popular involvement; state and political organisation; trade unions; transformation; alliansie; bevrydingsbeweging; burokrasie; demokrasie; Kommuniste; korrupsie; krisis; leierskapstryd; onderhandelings; populêre betrokkenheid; regering; sentralisasie; staatsen politieke organisasie; transformasie; vakbonde